2015
DOI: 10.17795/zjrms-1053
|View full text |Cite
|
Sign up to set email alerts
|

The Antibacterial Activity of SnO2 Nanoparticles against Escherichia coli and Staphylococcus aureus

Abstract: Background: An increasing amount of populations all over the world are reported to have no access to clean and fresh water. Some traditional chemical disinfectants (free chlorine, chloramines, and ozone) are already widely used in the water industry; alarmingly, many of these are carcinogens. Furthermore, the resistance of microorganisms to these common chemical disinfectants is increasing; superior alternatives are therefore necessary. The development of nanoscience and nanotechnology within the last decades … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 33 publications
2
24
0
2
Order By: Relevance
“…The above data guarantees with the previous research which has been conducted with the SnO 2 nanoparticles studies [38]. Nanoparticles exerts its anti-microbial activity by breaking the cell wall membrane and thereby causing disturbance in the cell functioning [44]. Previously, studies have reported that tin oxide nanoparticles possess significant antimicrobial activity [18].…”
supporting
confidence: 88%
See 1 more Smart Citation
“…The above data guarantees with the previous research which has been conducted with the SnO 2 nanoparticles studies [38]. Nanoparticles exerts its anti-microbial activity by breaking the cell wall membrane and thereby causing disturbance in the cell functioning [44]. Previously, studies have reported that tin oxide nanoparticles possess significant antimicrobial activity [18].…”
supporting
confidence: 88%
“…The zone of inhibition was measured in mm and was found to be 35 mm for calcinated SnO 2 nanoparticles against Klebsiella and 18mm for the same against S. aureus (Table III). The lower concentration of nanoparticles didn't give much promising result against the microbes [33], [34].…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Kumar 2017, also reported that SnO 2 NPs, bind to the outer membrane, thereby inhibiting the growth of Pseudomonas and Staphylococcus aureus, which goes in agreement with the studies conducted by Raj et al. and Amininezhad et al ,…”
Section: Resultsmentioning
confidence: 99%
“…In gram-negative bacteria E. coli, the plasma membrane is surrounded by a cell wall composed of peptideoglycan, followed by an outer membrane of proteins, lipids and lipopolysaccharides. Its structure is often thinner than the cell wall of gram-positive bacteria S. aureus (Feng Amininezhad et al (2015). According to Rinc on and Pulgarin (2004), certain bacteria, especially gram-positive, have a very viscous capsule, which functions as a protection to the cellular wall.…”
Section: Ag þmentioning
confidence: 99%